Nova Scotia’s Deemed Consent for Deceased Organ Donation: Family Member Perspectives and Experiences in the ICU Setting - Aimee J. Sarti, MD; Stephanie Sutherland, PhD; Matthew J. Weiss, MD; Alain Landry, BScN; Heather Hemming, MSW; Jade Dirk, BSc; Ken Lotherington, BA; Stephen Beed, MD (Transplantation Direct)
Background. The purpose of this study was to explore the experience of family members of potential organ donors in the intensive care unit following the change to deemed consent legislation in Nova Scotia. Methods. This was a qualitative study with semistructured, in-depth interviews with 17 family members who were asked to make an organ donation decision on behalf of patients admitted to the intensive care unit in Nova Scotia. We analyzed themes using a descriptive approach. Participants were recruited from the organ donation organization in Nova Scotia, Canada. Results. Participant awareness and knowledge of the Human Organ and Tissue Donation Act legislation varied from individuals having no awareness and knowledge of the bill to those who had awareness and optimism that the legislation would be beneficial for increasing organ donation rates in the province. Other themes emerging from the interviews included (1) COVID context, (2) quality of healthcare professional care, (3) family support, and (4) barriers to donation (waiting, consent questionnaire, and patient transfers). Conclusions. The Human Organ and Tissue Donation Act legislation included enhanced support, which was viewed positively by family members. There is a need for continued evaluation as most participants felt it was too early to see the tangible impacts of the newly implemented legislation.